Combined prediction value of coronary plaque burden, serum creatinine, MLR and NLR in reinfarction risk after PCI in middle-aged and elderly patients with myocardial infarction - Huanhua Du; Zheng Lu; Yutong Liu; Jinsong Yan; Junli Ma; Jili Ao; Gang Chen (European Journal of Medical Research, 2025)
Abstract Objective To analyze the predictive value of coronary plaque burden combined with serum creatinine (Scr), monocyte/lymphocyte ratio (MLR), and neutrophil/lymphocyte ratio (NLR) in the risk of reinfarction after percutaneous coronary intervention (PCI) in middle-aged and elderly patients with acute myocardial infarction (AMI). Methods A retrospective analysis was conducted on the clinical data of 1,582 patients with AMI who underwent PCI in our hospital from January 2021 to January 2024. Based on the occurrence of reinfarction within 6 months post-PCI, patients were divided into a reinfarction group (216 cases) and a non-reinfarction group (1,366 cases). To analyze the risk factors and related predictive values of reinfarction in middle-aged and elderly AMI patients after PCI. Results Multivariate Logistic regression analysis showed that age, Killip grade, LVEF, cTnI, non-calcified plaque burden, calcified plaque burden, total calcified plaque burden, Scr, MLR, and NLR were all risk factors for reinfarction in middle-aged and elderly AMI patients after PCI (P < 0.05). ROC analysis showed that the combined detection of coronary plaque burden, Scr, MLR and NLR predicted the risk of reinfarction in middle-aged and elderly AMI patients after PCI, and the AUC was 0.998, 95%CI was 0.997 ~ 1.000, the sensitivity was 99.10%, and the specificity was 97.20%, all of them were significantly higher than the individual detection of each index (P < 0.05). Conclusion The combined detection of coronary plaque burden, Scr, MLR and NLR has a high predictive value for reinfarction after PCI in middle-aged and elderly AMI patients, and should be paid close attention to clinically.